Comparison of Anti-oncotic Effect of TRPM4 Blocking Antibody in Neuron, Astrocyte and Vascular Endothelial Cell Under Hypoxia - Wei, Shunhui; Low, See Wee; Poore, Charlene Priscilla; Chen, Bo; Gao, Yahui; Nilius, Bernd; Liao, Ping (Frontiers in Cell and Developmental Biology, 2020)
In stroke and other neurological diseases, Transient Receptor Potential Melastatin 4 (TRPM4) has been reported to cause oncotic cell death which is due to an excessive influx of sodium ions. Following stroke, hypoxia condition activates TRPM4 channel, and the sodium influx via TRPM4 is further enhanced by an increased TRPM4 expression. However, the effect of TRPM4 inhibition on oncotic cell death, particularly during the acute stage, remains largely unknown. Recently, we have developed a polyclonal antibody M4P that specifically inhibits TRPM4 channel. M4P blocks the channel via binding to a region close to the channel pore from extracellular space. Using M4P, we evaluated the acute effect of blocking TRPM4 in neurons, astrocytes, and vascular endothelial cells. In a rat stroke model, M4P colocalized with neuronal marker NeuN and endothelial marker vWF, whereas few GFAP positive astrocytes were stained by M4P in the ipsilateral hemisphere. When ATP was acutely depleted in cultured cortical neurons and microvascular endothelial cells, cell swelling was induced. Application of M4P significantly blocked TRPM4 current and attenuated oncosis. TUNEL assay, PI staining and western blot on cleaved Caspase-3 revealed that M4P could ameliorate apoptosis after 24 hours hypoxia exposure. In contrast, acute ATP depletion in cultured astrocytes failed to demonstrate an increase of cell volume, and application of M4P or control IgG had no effect on cell volume change. When TRPM4 was overexpressed in astrocytes, acute ATP depletion successfully induced oncosis which could be suppressed by M4P treatment. Our results demonstrate that comparing to astrocytes, neurons and vascular endothelial cells are more vulnerable to hypoxic injury. During the acute stage of stroke, blocking TRPM4 channel could protect neurons and vascular endothelial cells from oncotic cell death.